The Influence of Happiness at Work and Work Spirituality on Organizational Citizenship Behavior in JABODETABEK - Aisy, Shaffaa Rihidatta; Archianti, Puti (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This research aims to test the empirical model of organizational citizenship behavior, work happiness and work spirituality in JABODETABEK employees. In this study the sample size was 300 employees who worked in Jakarta, Bogor, Depok, Tangerang & Bekasi (JABODETABEK) area. Sampling used Google form (Questionnaire). The research test used is the Multiple Regression Test. Based on the research results that have been obtained, it can be concluded that the work happiness and work spirituality positively influences work happiness and work spirituality in JABODETABEK employees. The magnitude of the influence is 62,7%. organizational citizenship behavior influences organizational citizenship behavior. Organizational citizenship behavior also positively influences Happiness Of Work and Work Of Spirituality. This can be interpreted as the higher the job happiness and work spirituality, the higher the organizational citizenship behavior, then the lower the job happiness and work spirituality, the lower the organizational citizenship behavior.